Asthma Worsenings: Approaches to Prevention and Management from the Asthma Worsenings Working Group - Meyer Balter; Pierre Ernst; Wade Watson; Harold Kim; Lisa Cicutto; Marie-France Beauchesne; Andrew J Cave; Alan Kaplan; Donna Hogg; Andrew McIvor; Tom Smiley; Michel Rouleau; et al. (Canadian Respiratory Journal)
Most asthma patients prescribed maintenance asthma therapies still experience periods of asthma worsenings characterized by daytime or nighttime symptoms, or an increased need for rescue medication. In fact, these episodes are highly prevalent even in patients with well-controlled disease. Published literature suggests that asthma worsenings likely represent a window of opportunity during which patients could intervene early to prevent exacerbations or further deterioration of asthma symptoms. However, current evidence suggests that most patients fail to respond or to self-manage appropriately during these periods.